Cultural Diversity Education in “Islam and Religious Moderation” Courses: Case Study in Islamic Higher Education - Karnadi; Hasanah, Silviatul; de Cómputo, Escuela Superior; Wilson, Elaine (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
This study investigates the implementation model of cultural diversity education within the  "Islam and Religious Moderation" courses in Islamic higher education institutions. The  increasing urgency to foster inclusive and tolerant attitudes among students in response to  plural religious and cultural realities drives the research. Positioned within the broader  discourse on religious moderation and educational transformation, this study seeks to explore  how pedagogical strategies can cultivate intercultural understanding grounded in Islamic  values. Employing a qualitative narrative inquiry approach, data were collected through  interviews, focus group discussions, and classroom observations, then analyzed using the  Clandinin three-phase model of filtering, grouping, and interpreting narrative data. The  findings reveal a three-stage implementation model: (1) building a comprehensive  understanding of religious moderation concepts contextualized in global and local frameworks;  (2) linking conceptual knowledge to lived experiences through reflective and dialogical  learning; and (3) promoting moderate behavior via project-based learning, guided discussions,  and critical engagement with case studies. The study concludes that integrating cultural  diversity into Islamic religious education can effectively reinforce students' inclusive religious  worldviews and foster mutual respect in campus life and society. These findings offer  pedagogical insights for embedding religious moderation into the curriculum as a  transformative force for pluralistic coexistence.